Aldo-keto Reductase 1B10 Restrains Cell Migration, Invasion, and Adhesion of Gastric Cancer via Regulating Integrin Subunit Alpha 5 - Yao, Haibo; Hu, Junfeng; Shao, Yanfei; Shah, Qinshu; Zheng, Shusen (Turkish Journal of Gastroenterology, 2023)
Background/Aims: Gastric cancer is a prevalent malignancy with unfavorable prognosis partially resulting from its high metastasis rate. Clarifying the molecular mechanism of gastric cancer occurrence and progression for improvement of therapeutic efficacy and prognosis is needed. The study tended to delineate the role and regulatory mechanism of aldo-keto reductase 1B10 (AKR1B10) in gastric cancer progression. Materials and Methods: The relationship of AKR1B10 expression with survival rate in gastric cancer was analyzed through Kaplan–Meier analysis. The mRNA levels of AKR1B10 and integrin subunit alpha 5 (ITGA5) in gastric cancer tissues and cell lines were measured by real-time quantitative polymerase chain reaction. Protein levels of AKR1B10 and integrin subunit alpha 5 were assayed via western blot. The molecular relationship between AKR1B10 and ITGA5 was analyzed by co-immunoprecipitation assay. Cell viability was assayed through Cell Counting Kit-8, invasion and migration of tumor cells was assessed through wound healing and transwell assays. Transwell assay was utilized to detect invasion. The adhesion of gastric cancer cells was detected using cell adhesion assays. Results: The results unveiled that integrin subunit alpha 5 was upregulated, while AKR1B10 was downregulated in gastric cancer tissues and cells. Overexpressing AKR1B10 hindered gastric cancer cell proliferation, migration, invasion and adhesion. It was striking that we certified the inhibitory effect of AKR1B10 on integrin subunit alpha 5 expression and their (AKR1B10 and ITGA5)) negative relationship via bioinformatics method, real-time quantitative polymerase chain reaction, and co-immunoprecipitation assays. Via rescue experiments, it was concluded that AKR1B10 served as tumor suppressor potentially by ITGA5 expression in gastric cancer. Conclusion: Our results indicated that AKR1B10 inhibited migration, invasion, and adhesion of gastric cancer cells via modulation of ITGA5.